2013
DOI: 10.1111/adb.12065
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a compulsive-like behavior in rats exposed to alternate access to highly preferred palatable food

Abstract: Converging evidence suggests that recurrent excessive calorie restriction causes binge eating by promoting behavioral disinhibition and overeating. This interpretation suggests that cognitive adaptations may surpass physiological regulations of metabolic needs after recurrent cycles of dieting and binging. Intermittent access to palatable food has long been studied in rats, but the consequences of such diet cycling procedures on the cognitive control of food seeking remain unclear. Female Wistar rats were divi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
45
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 51 publications
6
45
0
Order By: Relevance
“…Targeting neural reward systems may also, in turn, result in a selective suppression of appetite for certain types of highly reinforcing foods. Findings from our laboratory and others have revealed that overconsumption, or binge consumption, of sugars and fats can lead to brain and behavioral changes similar to those seen within the context of drug addiction, providing empirical support for the concept of food addiction (Avena et al, 2008; Oswald et al, 2011; Iemolo et al, 2012; Rossetti et al, 2013). Such findings point to one potential reason that weight loss may be so challenging for some, but also provide an avenue to study potential treatments that consider and address the effects that these ingredients can have on the brain.…”
supporting
confidence: 57%
“…Targeting neural reward systems may also, in turn, result in a selective suppression of appetite for certain types of highly reinforcing foods. Findings from our laboratory and others have revealed that overconsumption, or binge consumption, of sugars and fats can lead to brain and behavioral changes similar to those seen within the context of drug addiction, providing empirical support for the concept of food addiction (Avena et al, 2008; Oswald et al, 2011; Iemolo et al, 2012; Rossetti et al, 2013). Such findings point to one potential reason that weight loss may be so challenging for some, but also provide an avenue to study potential treatments that consider and address the effects that these ingredients can have on the brain.…”
supporting
confidence: 57%
“…A similar decreased reward system functioning is also observed in obesity-prone rats, prior to the development of obesity (Valenza et al, 2015), indicating that the decreased reward system functioning is both a vulnerability factor (Valenza et al, 2015) as well as a consequence of the overconsumption of palatable food (Johnson and Kenny, 2010). Renewing access to palatable food following abstinence induces overconsumption of palatable food (Avena et al, 2008a;Colantuoni et al, 2002;Cottone et al, 2009b;Rossetti et al, 2014), and this renewed access is able to relieve withdrawalinduced depressive and anxiety-like behaviors (Iemolo et al, 2012). Thus, evidence from animal models strongly suggests that pathological eating can contribute to the emergence of a negative emotional state, and that relief of anxiety or stress can drive compulsive eating behavior.…”
Section: Overeating To Relieve a Negative Emotional Statementioning
confidence: 69%
“…The procedure described here in female rats has the advantage of being considerably faster than previously established protocols of palatable diet alternation (Hagan et al , 1997; Cifani et al , 2009; Cottone et al , 2009b; Rossetti et al , 2013). In addition, our results show that withdrawal from alternating access to the palatable diet makes individuals vulnerable to the anxiogenic effects of rimonabant.…”
Section: Discussionmentioning
confidence: 99%